Analysis of Surveillance Systems in Place in European Mediterranean Countries for West Nile Virus (WNV) and Rift Valley Fever (RVF). (November 2013) - Cito, F.; Narcisi, V.; Danzetta, M. L.; Iannetti, S.; Sabatino, D. D.; Bruno, R.; Carvelli, A.; Atzeni, M.; Sauro, F.; Calistri, P.
Summary: West Nile virus (WNV) and Rift Valley fever virus (RVFV) represent an important group of viral agents responsible for vector‐borne zoonotic diseases constituting an emerging sanitary threat for the Mediterranean Basin and the neighbouring countries. WNV infection is present in several Mediterranean countries, whereas RVF has never been introduced into Europe, but it is considered a major threat for North African countries. Being vector‐borne diseases, they cannot be prevented only through an animal trade control policy. Several approaches are used for the surveillance of WNV and RVFV. With the aim of assessing the surveillance systems in place in Mediterranean countries, two disease‐specific questionnaires (WNV, RVFV) have been prepared and submitted to Public Health and Veterinary Authorities of six EU countries. This study presents the information gathered through the questionnaires and describes some critical points in the prevention and surveillance of these diseases as emerged by the answers received.